Environmental History and World History - Bao Maohong (Historia provinciae: журнал региональной истории, 2018)
This paper deals with three major aspects of world environmental historiography. Firstly, based on a bird’s-eye view of the world environmental historiography, the ‘received wisdoms’ were deconstructed. Secondly, observing from three schools of world history incorporated with the new thinking of the environmental history, four main contributions of environmental history to the world historiography were figured out. Thirdly, this paper predicts that the future of environmental history depends on the balance of five pairs of relations that regulate the nature and the path of the environmental history.